New Results on the Control for a Kind of Uncertain Chaotic Systems Based on Fuzzy Logic - Bo Wang; L. L. Chen (Complexity)
In this paper, the problem of the control for an uncertain nonlinear chaotic system has been studied; based on fuzzy logic, a kind of single-dimensional controller is constructed for the control of the chaotic systems in the situation that uncertainties and unknowns exist; at last some typical numerical simulations are carried out, and corresponding results illuminate the effectiveness of the controller.